Sexual Predators Amongst Us. - Rufo, Ronald A. (CRC Press, 2011)
Characteristics of a Sexual Predator Sexual Predators-What Are We Dealing With? Causes of Sexual Violence Characteristics and Patterns Cognitive Behavioral Theories The Social Bond Theory Profile of a Female Sexual OffenderProfile of a Male Sexual Offender In My Opinion: Dr. Laura BarrowGrooming the Victim Grooming Progression of Behavior for Grooming a Victim Children Not Coming Forward Parental/Predator Abuse and Emotional Blackmail and Guilt Profile of a Female Sex Offender Profile of a Male Sex Offender In My Opinion: Ms. Maryanne LeachChild Abuse and Incest Child Abuse Sexual Abuse of a C.